Policy mobilities and methodology: a proposition for inventive methods in education policy studies. Issue 2 (4th May 2017) - Gulson, Kalervo N.; Lewis, Steven; Lingard, Bob; Lubienski, Christopher; Takayama, Keita; Webb, P. Taylor
ABSTRACT: The argument of this paper is that new methodologies associated with the emerging field of 'policy mobilities' can be applied, and are in fact required, to examine and research the networked and relational, or 'topological', nature of globalised education policy, which cuts across the new spaces of policymaking and new modes of global educational governance. In this paper, we examine the methodological issues pertaining to the study of the movement of policy. Informed by contemporary methodological thinking around social network analysis and the ethnographic notion of 'following the policy', we discuss the limitations of these approaches to adequately address presence in policy network analysis, and the problem of representing speed and intensity of policy mobility, even while these attempt to solve the problem of relationality and territoriality. We conclude that the methodologies of policy mobility are inexorably intertwined with the (constantly) changing phenomena under examination, and hence require what Lury and Wakeford describe as 'inventive methods'.